Community Milieu Approach: Resource for Criminal Justice System - Knox, Peter (1976)
Never before in our history has there been such a need for sophisticated programming to deal with the deviant patterns of behavior that are becoming so prevalent in our society. Violent acting out, and a myriad of other self-destructive and socially unacceptable behaviors are emerging which demand immediate attention. This article is devoted to describing the approach of a community-based counseling/rehabilitative program that has responded to the dilemma. Adolescent Counseling in Development was created several years ago to answer the specific need of a community experiencing a tremendous increase in the use and abuse of drugs. The program has continued to grow and modify it's methods to meet the various needs that are emerging almost daily. The key element of this program design is that it functions within the community and is tied into the various systems that deal with the delinquent, the youthful offender, and other acting-out persons within the confines of three large urban communities. Adolescent Counseling in Development originated in 1969, under the auspicies of Father Bernard Lane, and as noted by it's acronym AcID , was geared to treat primarily persons experiencing drug problems. However, as the agency developed, multiple program elements were created, that, in essence, met the needs of the community as a functioning unit and the specific needs of individuals within the community. In time, AcID has grown to be a multifaceted program that now maintains a staff of over fifty persons, services five communities and focuses major emphasis on servicing and being a part of the Criminal Justice System